Dielectric properties of UV-irradiated ultrathin polysulfone films revealed by surface plasmon resonance method. Issue 4 (19th May 2018) - Pogreb, Roman; Danchuk, Viktor; Whyman, Gene
ABSTRACT: The surface plasmon resonance research of manufactured highly homogeneous ultrathin polysulfone films was performed, which were exposed to the short-wave (254 nm) UV irradiation of various durations. Surprisingly, the resonance incident angle and dielectric constant increase after short-term UV irradiation before the ordinary decrease caused by usual polymer degradation. The experimental results are ascribed to the formation of polar groups leading to orientation of chain fragments of intermediate length followed by their breaking and formation of mobile short fragments under longer times of irradiation.